Mode of Entry into Hybrid Entrepreneurship: New Venture Start-Up versus Business Takeover - Guoqian Xi; Jörn Block; Frank Lasch; Frank Robert; Roy Thurik (Institute of Labor Economics (IZA), 2017)
Many entrepreneurs start their ventures while retaining jobs in wage employment; this phenomenon is called hybrid entrepreneurship. Little is known about the entry modes (new venture start-up vs. business takeover) of hybrid entrepreneurs. Our study aims to close this gap by investigating the path to hybrid entrepreneurship. Using a large sample of French hybrid entrepreneurs, we show that educational attainment and management experience are associated with new venture start-up, whereas being female, having worker experience, and having received social benefits are linked to business takeover. With these results, our study contributes to research on hybrid entrepreneurship and entrepreneurship entry modes. Moreover, it informs policy makers about the nature of hybrid entrepreneurship and contributes to the design of effective policies to promote business takeover, which is of high interest, given the growing number of businesses seeking outside successors.
Keywords: L26; 330; hybrid entrepreneurship; entrepreneurship entry mode; business takeover; new venture